Subxiphoid video-assisted major lung resections: the Believers’ speech - Aresu, Giuseppe; Jiang, Lei; Bertolaccini, Luca (Journal of Thoracic Disease, 2017)
Commentary from Terzi and Viti (1) on the subxiphoid lung resections papers presented by Hernandez-Arenas et al. (2) underlined some limitations of this approach but are those limits real and still unresolved and are them going to stop its spread? There is a natural evolution and optimisation of the new techniques; this is what we have experienced for several minimally invasive procedures including the uniportal video-assisted thoracoscopic surgery (VATS) at first indicated even by Gonzalez as suitable just for lower lobectomies (3). This is what, in contradiction with the speeches of the skeptics, we predict we will experience for the subxiphoid lung resections. Therefore, we would like to readdress the attention and reanalyze some of the points examined by the two authors.